Climate-smart livestock management - Gosling, Amanda; Center for International Forestry Research and World Agroforestry (2024)
This poster defines climate-smart agriculture (CSA) and explains its three interlinked pillars. It provides climate change mitigation and adaptation measures that can be adopted by the livestock sector and how they relate to the three pillars of CSA. The poster forms part of the Climate-Smart Forage and Feed Innovations training package that was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzania and Malawi teams to accelerate the spillover process of validated AICCRA technologies. The poster content is based on knowledge materials sourced from the AICCRA Ethiopia team.